Effective Management of a Fractured Tooth in a Child Using an Aesthetic Pediatric Crown: A Case Report and Review of Literature - Stephan Lampl; Deepa Gurunathan; Deepak Mehta; Jogikalmat Krithikadatta; Desigar Moodley (Case Reports in Dentistry)
Conclusion: The case highlights successful conservative restoration in mixed dentition using a pediatric full crown with a hybrid glass material. This approach achieved functional and aesthetic improvements, preserved tooth vitality, and ensured patient satisfaction.